Urban toys as a new alternative media to promote Indonesian culture - Oktaviani, Rani Chandra; Ichwan, Fadlin Nur (Penerbit Universiti Kebangsaan Malaysia, 2018)
There is a phenomenon in Indonesian society which is currently more interested in popular culture, such as from Korea, Japan, USA and other developed countries. This is also the impact of aggresive promotions from developed countries’ popular culture through film, music, drama and other media. One of the popular culture products that also entered Indonesia is urban toys. In the midst of urban toys, the emergence of an Indonesian urban toy designer who joined the community with the name IAT (Indonesian Art Toys) has placed idealism on their artworks to promote Indonesian culture through urban toys. By bringing the culture in the mirror theory, supported by the concept of promotion mix, toy literature and communication, and using qualitative methodology, this research aims to analyze and explore the position, strength and weakness of urban toys as a new alternative media for promoting Indonesian culture. The results show that urban toys hold the position as products as well as a media for cultural promotion. The strength of this culture of media promotion lies in the combination of visualization of traditional cultural artifacts with packaging of pop culture, so that it has added value and opens up new market segments. However, currently the work of urban toys has not been produced on a mass scale by producers, because it is still produced by artists individually. This study concludes that urban toys can play a role as a new alternative media for the culture of visual communication and bring national cultural identity.